State government budget stabilization : policy, tools, and impacts - Hou, Yilin (Studies in Public Choice, 2013)
This book is the first comprehensive, full-scale treatment of the law, politics and economics with regard to the policies and policy instruments for budget stabilization at the state level. Covering the period from 1946 through 2008 in the United States, it provides details on the methods and results of empirical tests of the effects of budget stabilization instruments on government operations, public service provision, and some other aspects of social and economic life. With the lingering effects of the most recent financial crisis and economic downturn, and the subsequent Tea Party movement advocating smaller government and deficit reduction, this book carries timely and important theoretical as well as practical implications, particularly in regard to the potential for counter-cyclical fiscal policy in mitigating negative impacts during a recession. The first contribution of the book is in public finance theory: it provides insights into the applications of the stabilization function in the context of strong government, thereby refining Keynesianism. The second aspect is in Public Choice: the creation and functioning of budget stabilization funds offer extra evidence to demonstrate that the general public provides input and voice in more than the conventional ways when it comes to policy making, even in an area dominated by strong government. The third aspect is in policy making, exploring the opportunities for refining policy tools in preparation for future downturns.